IMPLEMENTASI KEBIJAKAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT(PNPM) MANDIRI PERDESAAN KABUPATEN DAIRI - PIN PIN . (LP2MTBM MAKARIOZ, 2020)
Policy Implementation in Dairi Regency has different characteristics so that dairi district government program in empoweringthe community, especially through the National Program of Community Empowerment (PNPM) Mandiri needs to be adaptedto the characteristics of each region. In this case, the Dairi Regency Government has not paid attention to the needs of thecommunity and only made its own decisions in the implementation of PNPM. Thus, there needs to be an assessment of theprograms that have been implemented in three locations and study the positive or otherwise impact felt by the localcommunity. The results of this study found a discrepancy in the distribution of PNPM Mandiri assistance in the form of theprocurement of reading parks, while what the community needs is the procurement of clean water because the surroundingwells are experiencing drought. PNPM Mandiri assistance in the form of different programs channeled by Kabuaten DairiGovernment is used to build community settlements. If viewed from the information that has been obtained the distribution ofpnpm mandiri assistance funds. Dairi District Government should pay more attention to the community by holding a smalldiscussion forum that invites RT, RW, and influential community leaders so that the Dairi Regency Government canunderstand the proposals of local residents.